Avaliação do efeito terapêutico do fluconazol no tratamento da Leishmaniose Tegumentar Americana: estudo preliminar - Oliveira, Judite Maria da Silva Costa de (2014)
The Leishmaniasis, a major public health problem worldwide consists of cutaneous, mucosal and visceral syndromes, caused by around 20 Leishmania species. In the American continente, cutaneous form is known as American Cutaneous Leishmaniasis (ACL). In Brazil, ACL has been detected in all federation’s units.The classic treatment is based on penthavalent anthimonial agent, only for parenteral administration, in which severe toxicity and side effects are frequently observed. Fluconazole is available for oral administration and is well tolerated. This is a lowest cost treatment, providing increased medication adherence and reducing the risk of resistant strains and mucosal form. The purpose of the study is to assess the therapeutic effect of fluconazole compared to the standard drug (Stibogluconate meglumine) regarding the healing time in both treatments. This is a descriptive, cross-sectional study based on data obtained retrospectively from ACL patients from Hospital São José de Doença Infecciosas (HSJ), Fortaleza-Ce, from 2009 to 2013. Patients were distributed as: group I (therapy with oral Fluconazole 8 mg/kg per day, N = 23) and group II (therapy with Stibogluconate meglumine, N = 13). They were evaluated with respect to epidemiological and clinical characteristics and outcome and the groups were homogeneous, except to the duration of the disease (p=0,019). In the Group I (therapy with oral fluconazole) the mean duration of disease was 3.0 months (min-max = 1-16 months) and in the Group II (therapy with Stibogluconate meglumine) was 1.5 months (min-max = 0.5 - 3 months) (p = 0.019). Among the patients treated with fluconazole, 21 patients (91.30%) were cured and in Stibogluconate meglumine group were 12 patients (92.3%). No response was observed in 2 Group I patients (8.69%) and in 1 Group II patient (7.7%). Referring to healing time, there was no statistically significant difference between groups. The mean healing time was 7.5 weeks in Group I (therapy with oral fluconazole) and 5 weeks in Group II (therapy with Stibogluconate meglumine) (p = 0.0713). Group I (therapy with oral fluconazole) at a dose of 8mg /kg per day was the cure rate was similar to that presented by Stibogluconate meglumine group. Fluconazole was well tolerated and is a good choice for LTA due to L. braziliensis.